P70 Association between built environment and cardiovascular diseases. (3rd September 2019) - Lee, EY; Choi, J; Lee, S; Choi, BY
Abstract : Background: Although increasing interest in the role of built environments that can influence residents' health and health behavior, little is known about the relationship between built environment and cardiovascular diseases (CVD). Therefore, this study was carried out to examine the association between objective measured built environment and CVD among adults in Gyeonggi province, Korea. Methods: A total of 50, 958 individuals living in 546 administrative districts of Gyeonggi province were analyzed. Individual data were obtained from the Korean Community Health Survey (KCHS). The CVD outcomes were self-reported history of physician diagnosis of hypertension, dyslipidemia, myocardial infarction, angina, and stroke. Built environment measures were created for 546 administrative districts of Gyeonggi province using Korean government databases (National Public Physical Activity Facility Database 2013, Korean Transport Database, Population Census 2013 and National Building Database 2013) and ArcGIS software. A Bayesian spatial multilevel model was implemented separately by age group (i.e. 40–50 years or ≥ 60 years). Results: After considering the individual- and neighborhood-level factors as well as the spatial variation in the model, living in neighborhoods with a middle-level distance to physical activity facilities (T2) was associated with 11.3% increased odds for CVD in elderly people over 60 years, compared with living in neighborhoods nearest to physical activity facilities (OR=1.11, 95% CI=1.003–1.236 for T2 vs. T1). For adult 40–59 years, no built environment significantly influenced CVD. Conclusion: The findings suggest that built environment that provided more opportunities for physical activity was negatively associated with CVD, practically in elderly people. Further research to examine the spatio-temporal association is needed to better understand the causality of the relationship between built environment and CVD.